Five years' experience with value-based quality improvement teams: the key factors to a successful implementation in hospital care - Kirsten Daniels; Marc B. V. Rouppe van der Voort; Douwe H. Biesma; Paul B. van der Nat (BMC, 2022)
Abstract Background In recent years, value-based healthcare (VBHC) has become one of the most accepted concepts for fixing the 'broken' healthcare systems. Numerous hospitals have embraced VBHC and are trying to implement value-based quality improvement (VBQI) into their practice. However, there is a lack of knowledge on how to practically implement VBHC and organizations differ in their approach. The aim of this study was to explore the main factors that were experienced as hindering and/or supporting in the implementation of VBQI teams in hospital care. Methods A qualitative study was performed with semi-structured interviews with 43 members of eight VBQI teams in a large Dutch top-clinical teaching hospital. Participants included physicians, physician assistants, nurses, VBHC project leaders, managers, social workers, researchers and paramedics. Interview grids were structured according to the RE-AIM model (reach, effectiveness, adoption, implementation and maintenance). A thematic content analysis with open coding was used to identify emerging (sub)themes. Results We identified nine main factors divided over three domains (organization, culture and practice) that determined whether the implementation of VBQI teams was successful or not: 1). Practical organization of value-based quality improvement teams, 2). Organizational structure 3). Integration of VBHC with existing quality improvement approaches and research 4). Adoption and knowledge of the VBHC concept in the hospital 5). Multidisciplinary engagement 6). Medical leadership 7). Goal setting and selecting quality improvement initiatives 8). Long-cycle benchmarking and short-cycle feedback 9). Availability of outcome data. Conclusions Overall, this study goes beyond the general VBHC theory and provides healthcare providers with more detailed knowledge on how to practically implement value-based quality improvement in a hospital care setting. Factors in the 'organization' and 'practice' domain were mentioned in the strategic value agenda of Porter and Lee. Though, this study provides more practical insight in these two domains. Factors in the 'culture' domain were not mentioned in the strategic value agenda and have not yet been thoroughly researched before.